Long-term cost reduction of routine medications following a residential programme combining physical activity and nutrition in the treatment of type 2 diabetes: a prospective cohort study. Issue 4 (16th April 2017) - Lanhers, Charlotte; Walther, Guillaume; Chapier, Robert; Lesourd, Bruno; Naughton, Geraldine; Pereira, Bruno; Duclos, Martine; Vinet, Agnès; Obert, Philippe; Courteix, Daniel; Dutheil, Frédéric
Abstract : Objectives: To demonstrate that lifestyle modifications will reduce the cost of routine medications in individuals with type 2 diabetes (T2D), through a mechanism involving glycaemic control. Design: A within-trial cost-medication analysis with a 1-year time horizon. Setting: Controlled environment within the spa resort of Chatel-Guyon, France. Participants: Twenty-nine participants (aged 50–70 years) with T2D. Interventions: A 1-year follow-up intervention, beginning with a 3-week residential programme combining high exercise volume (15–20 hours/week), restrictive diet (−500 kcal/day) and education. Participants continued their routine medication, independently managed by their general practitioner. Main outcome measures: Number of medications, number of pills, cost of medications and health-related outcomes. Results: Twenty-six participants completed the 1-year intervention. At 1 year, 14 patients out of 26 (54%) stopped/decreased their medications whereas only 5 (19%) increased or introduced new drugs (χ 2 =6.3, p=0.02). The number of pills per day decreased by 1.3±0.3 at 12 months (p<0.001). The annual cost of medications for T2D were lower at 1 year (€135.1±43.9) versus baseline (€212.6±35.8) (p=0.03). The regression coefficients on costs of routine medication were 0.507 (95% CI 0.056 to 0.959, p=0.027) for HbA1c and 0.156 (95% CI −0.010 to 0.322, p=0.06) for blood glucose levels. Diabetics patients with HbA1c >6.5% in the highest (last) quartile doubled their routine medication costs (66% vs 33%, p=0.037). Conclusions: Individuals with T2D reduced routine medication costs following a long-term lifestyle intervention that started with a 3-week residential programme. Combining high exercise volume, restrictive diet and education effectively supported the health of T2D. The main factor explaining reduced medication costs was better glycaemic control, independent of weight changes. Despite limitations precluding generalisability, cost-effective results of reduced medication should contribute to the evidence base required to promote lifestyle interventions for individuals with T2D. Trial registration number: NCT00917917 ; Post-results.